A multicentre comparison of a fast track or conventional postoperative protocol following laparoscopic or open elective surgery for colorectal cancer surgery. (February 2014) - Esteban, F.; Cerdan, F. J.; Garcia‐Alonso, M.; Sanz‐Lopez, R.; Arroyo, A.; Ramirez, J. M.; Moreno, C.; Morales, R.; Navarro, A.; Fuentes, M.
Abstract Aim The introduction of multimodal or fast track (FT) rehabilitation and laparoscopy in colorectal surgery has improved patient recovery and shortened hospital stay (HS). This study aimed to determine the influence of laparoscopic or open surgery on the postoperative recovery of colorectal cancer patients having a conventional care (CC) or FT protocol in the postoperative period. Method A multicentre prospective study was controlled with a retrospective group. The prospective group included 300 patients having elective colorectal resection for cancer. The retrospective control group included 201 patients with the same characteristics who were treated before the introduction of the programme. The patients were divided into four groups including laparoscopy + FT, open surgery + FT, laparoscopy + CC, and open surgery + CC. The primary end‐points were HS and morbidity. Secondary end‐points included mortality and reoperation rates. Results The overall median HS was 7 days. The median HS for laparoscopy + FT was 5 days, open + FT 6 days, laparoscopy + CC 9 days and open + CC 10 days (P < 0.001). In the regression model the laparoscopy + FT group had the greatest reduction in HS (P < 0.001). A significant reduction in HS was observed in the laparoscopy + FT group compared with laparoscopy + CC (P < 0.001). The overall patient morbidity was 30.6%. The logistic regression model adjusted for propensity score showed no statistically significant differences between the study groups regarding all other end‐points. Conclusion Colorectal cancer patients who underwent laparoscopic surgery within a multimodal rehabilitation protocol experienced the shortest HS and the lowest morbidity.